Coupling Urinary Trihalomethanes and Metabolomic Profiles of Type II Diabetes: A Case-Control Study - Andrianou, Xanthi; Charisiadis, Pantelis; Makris, Konstantinos C. (My University, 2017)
Abiding by the exposome paradigm, incorporation of external and internal exposure metrics using metabolomics tools is warranted to refine the etiology of type II diabetes (T2D). A small (n = 51) age-and sex matched case-control study was conducted in Cyprus coupling urinary trihalomethanes (THMs) with T2D. The objectives were to (i) perform a comparative assessment of different deconvolution parameters in compound identification and (ii) evaluate the association between differentially expressed metabolites and either urinary THM or T2D status. Untargeted urinary metabolomics was performed with a GC MS triple quadrupole mass spectrometry system. Results of three deconvolution searches each yielding >130 metabolites were used in subsequent analyses. The number of differentially expressed compounds by T2D status or the urinary THM levels (above or below median) differed among the three searches. The identity of these compounds was also confirmed using known standards (level 1 identification). In multivariate logistic regression, 3-aminoisobutyric acid was an important predictor of lower odds of T2D after adjusting for known risk factors. The widespread incorporation of metabolomics in population studies accounting for environmental exposures will eventually pave the way for the exposome characterization, also improving our understanding of,the disease process.
Keywords: Metabolomics; Type 2 diabetes; Trihalomethanes; Exposures; Exposome